A study of teachers’ perceptions of the National Children’s Choir. - Logue, Gráinne (My University, 2021)
In 1985, Seán Creamer, a music inspector with the Department of Education and Science, established a choral programme in the Republic of Ireland: the National Children’s Choir [NCC]. The intention behind the NCC is to provide primary school children with the opportunity to enhance their music education, develop a love for choral singing, and to perform in concert. Since its inception, over 160,000 children have participated in the programme. It remains largely unstudied, however, and as such, its full effects and benefits are not fully understood. This study examines teachers’ perceptions of the NCC. Using qualitative methodology, the research data were collected using semi-structured interviews. Six teachers of various backgrounds were selected from three different schools to share their experiences of the NCC. The research was undertaken due the researcher’s particular passion for choral singing and belief in the importance of music education. This research explores the benefits and challenges of the NCC for children, how it impacts development of musical and personal skills, and how it contributes to their sense of confidence. In line with literature on the benefits of choral singing, the findings of this research reveal that participation in the programme improves children’s musical skills and leads to improved confidence and self-esteem levels. The research also examines the teachers’ own experiences of the programme, including the effectiveness of the resources provided, the importance of school support, and how teachers’ confidence levels in teaching music influence their experiences. The data reveal an overwhelmingly positive general opinion regarding the NCC and its value in the music education of primary school children. Recommendations for further research which emerged from the data include if low confidence levels in teachers exclude them from the NCC - and if so, if further continuous professional development is required - and if the demographic, culture, and location of a school impacts its experience of the NCC.
Keywords: The National Children’s Choir [NCC]; Irish Primary Schools; Music education; Choral singing; Choral societies; Primary education; Ireland; Choral singing